Optical and photoelectrical properties of the tetrathiotetracene-fullerene (TTTC₆₀) film heterostructures - Gorishny, M.P.; Verbitsky, A.B.; Kovalchuk, A.V.; Kovalchuk, T.N.; Lutsyk, P.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The optical and photoelectrical properties of heterostructures (HS) SnO₂ТTTC₆₀Ag are investigated. The additional absorption of HS ТTT and C₆₀ is revealed in comparison with those for their components, which testifies to the formation of complexes between the ТTT and C₆₀ molecules near the ТTT-C₆₀ interface. Currentvoltage characteristics (J-V) of a dark current is symmetric, as well as corresponds to the Ohm law for the voltages of 0 to 0.4 V. In the voltage range of 0.4 to 1.0 V, the branch of J-V at the positive polarity (I₊) goes above that at the negative polarity (I₋) at a SnO₂- electrode. Thus, in the double logarithmic scale, I₊ and I₋ are described by direct lines with the angular factors 1.77 and 1.37, accordingly, and exponents in the half-logarithmic coordinates (log I−U). The open-circuit voltage Voc has a positive polarity at the SnO₂- electrode irrespective of the illumination direction of a sample. Photovoltage is caused by antiblocking bends of bands for holes and electrons near the SnO₂- and Ag-electrodes of ТTT and C₆₀ films, accordingly. The dark effective specific resistance of the HS SnO₂ТTTC₆₀Ag is equal to 5·10⁷ Ohm·cm.